Streptomyces qinzhouensis sp. nov., a mangrove soil actinobacterium. Issue 3 (17th January 2020) - Zhu, Peng; Xu, Youhou; Fu, Jianjun; Liao, Yongyan
Abstract : A novel Streptomyces strain (SSL-25 T ) was isolated from mangrove soil sampled at QinzhouBay, PR China. The isolate was observed to be Gram-stain-positive and to form greyish-white aerial mycelia that differentiated into straight spore chains with smooth-surfaced spores on International Streptomyces Project 2 medium. The cell-wall peptidoglycan was determined to contain ll -diaminopimelicacid. The cell-wall sugars were glucose and mannose. The predominant menaquinones were MK-9 (H6), MK-9 (H8) and MK-9 (H4). The major polar lipids contained diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylinositol, phosphatidylinositol mannoside and several unidentified phospholipids. The predominant cellular fatty acids were C16:0, iso-C16:0 and summed feature 3 (C16:1 ω7 c /C16:1 ω6 c ). The genome size of strain SSL-25 T was 8.1 Mbp with a G+C content of 71.5 mol%. Phylogenetic analysis indicated that strain SSL-25 T is closely related to Streptomyces tsukubensis NRRL 18488 T (99.4 % sequence similarity). However, the digital DNA–DNA hybridization (39.8 %) and average nucleotide identity (91.3 %) values between them showed that it represents a distinct species. Furthermore, the results of morphological, physiological and biochemical tests allowed further phenotypic differentiation of strain SSL-25 T from S. tsukubensis NRRL 18488 T . Therefore, based on these results, it is concluded that strain SSL-25 T represents a novel Streptomyces species, for which the name Streptomyces qinzhouensis sp. nov. is proposed. The type strain is SSL-25 T (=CICC 11054 T =JCM33585 T ).